2005
DOI: 10.2214/ajr.184.3.01840887
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Detection of Amorphous Calcifications

Abstract: The CAD sensitivity for malignant amorphous calcifications is markedly lower than previously reported for all malignant calcifications. Breast imaging radiologists who use CAD systems should continue to search diligently for these difficult-to-detect lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 8 publications
4
14
2
Order By: Relevance
“…The rate of malignancy for amorphous microcalcifications is compatible with those reported by Berg et al [10] (20%), Soo et al [11] (16%) and Liberman et al [12] (26%). These results suggest that amorphous calcifications should be considered suspicious and referred for biopsy.…”
Section: Discussionsupporting
confidence: 90%
“…The rate of malignancy for amorphous microcalcifications is compatible with those reported by Berg et al [10] (20%), Soo et al [11] (16%) and Liberman et al [12] (26%). These results suggest that amorphous calcifications should be considered suspicious and referred for biopsy.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, d-CAD marked 96% of the malignant-like group presenting as amorphous calcifications measuring 1-7 mm extent and 95% of the malignant-like group measuring .7 mm (Table 3), which is higher than published results for d-CAD [22] for this size of group, and marked higher than indirect CAD applied in amorphous calcifications [12] or slightly higher when considering all types of microcalcifications [24] for equivalent extension measurements.…”
Section: Discussioncontrasting
confidence: 70%
“…We found a 29% risk of malignancy of the amorphous calcifications, and d-CAD detected 100% of the malignant cases or 96% of the malignant-like cases (breast cancer plus high-risk lesions). Berg et al [9] and Soo et al [12] found a 16-20% risk of malignancy in their series, and CAD case sensitivities by histological outcomes were found to be 57% for malignant calcifications, 29% for high-risk calcifications and 54% for benign calcifications. Their results are not akin to ours (100% for malignant calcifications, 85% for high-risk calcifications and 61% for benign calcifications) and this may represent the differences from using direct (our study) vs indirect CAD (with digitisation of images) systems.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations